Impact of the Herbal Breviscapine on the Pharmacokinetics of Simvastatin in Rats: The Involvement of CYP3A4 - Ju, Aixia; Li, Yang Yang; Qu, Zhe; Li, Qiuhong (Drug Research, 2017)
The effect of breviscapine injection on the pharmacokinetics of simvastatin and the mRNA expression of hepatic cytochrome P450 (CYP) enzyme was investigated with rats. The rats were pretreated for 8 consecutive days with breviscapine injection (20 mg/kg/day, i. v.), followed by administration of simvastatin through gavage (40 mg/kg). The control rats received the corresponding volume of saline solution for the pretreatment. Blood samples were collected at varied time points after simvastatin administration and the liver was harvested after the last collection of the blood sample for measurement of the CYP3A4 mRNA expression. Pre-treatment with breviscapine injection led to increased plasma concentration of simvastatin, showing 57% increase for AUC0-∞ (P<0.01), 31% increase for C max (P<0.01), and 36% decrease for the total plasma clearance, compared with the control. Pre-treatment with breviscapine injection also inhibited the mRNA expression of the hepatic CYP3A4. These findings indicate that pre-treatment with breviscapine injection could increase the plasma concentration of simvastatin, possibly by inhibiting the expression of the hepatic CYP3A4, and combined use of breviscapine with simvastatin may improve the simvastatin efficacy and reduce its adverse reactions through reduced its dosage.